2022
DOI: 10.3389/fpls.2022.926574
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Backbone Phylogeny and Character Evolution of Corydalis (Papaveraceae) Based on Plastome Data

Abstract: A robust backbone phylogeny is fundamental for developing a stable classification and is instructive for further research. However, it was still not available for Corydalis DC., a species-rich (> 500 species), ecologically and medically important, but taxonomically notoriously difficult genus. Here, we constructed backbone phylogeny and estimated the divergence of Corydalis based on the plastome data from 39 Corydalis species (32 newly sequenced), which represent ca. 80% of sections and series across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 85 publications
5
12
1
Order By: Relevance
“…Based on the high-quality data sets of 65 plastome CDS and 152 low-copy nuclear genes, we reconstructed the most complete phylogeny of Corydalis, including all sections and "series", which resulted in the most robust backbone relationships available to date. This contrasts with previous phylogenetic studies based on a few plastid regions and limited taxonomic sampling Wang, 2006;Zhang et al, 2016;Jiang et al, 2018;Li, 2018;Xu et al, 2022). Both nuclear and plastid data provided well resolved trees, but some topological incongruences were evident, primarily concerning branches with low support.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Based on the high-quality data sets of 65 plastome CDS and 152 low-copy nuclear genes, we reconstructed the most complete phylogeny of Corydalis, including all sections and "series", which resulted in the most robust backbone relationships available to date. This contrasts with previous phylogenetic studies based on a few plastid regions and limited taxonomic sampling Wang, 2006;Zhang et al, 2016;Jiang et al, 2018;Li, 2018;Xu et al, 2022). Both nuclear and plastid data provided well resolved trees, but some topological incongruences were evident, primarily concerning branches with low support.…”
Section: Discussioncontrasting
confidence: 90%
“…With 65 CDS of 280 plastomes (including 273 newly sequenced) and 152 low-copy nuclear genes of 278 samples (including 276 newly sequenced) of Corydalis, our analysis indicated that the genus is monophyletic and its sister group is the tribe Fumarieae represented by two genera in the plastid data and by seven genera in the nuclear data. The monophyly of Corydalis is congruent with previous studies based on a few plastid fragments and smaller taxonomic sampling Wang, 2006;Perez-Gutierrez et al, 2015;Xu and Wang, 2021;Xu et al, 2022). However, the larger taxonomic sampling in our study resulted in better support than in previous studies.…”
Section: Monophyly Of Corydalissupporting
confidence: 89%
See 2 more Smart Citations
“…Taxonomists have long considered the genus as a great challenge to classify because of its great variability. Early research proposed a classification system at section level based on only morphological evidence (Wu et al, 1996(Wu et al, , 1999, and recent molecular studies, were based on only a few markers and limited sampling (Wang, 2006;Zhang et al, 2008;Xu et al, 2022). These studies show both have indicated that the genetic relationships between most sections and species are unclear.…”
Section: De-yuan Hongmentioning
confidence: 99%